2011
DOI: 10.1016/j.ydbio.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C. elegans U2 snRNP protein MOG-2 in sex determination, meiosis, and splice site selection

Abstract: In Caenorhabditis elegans, germ cells develop as spermatids in the larva and as oocytes in the adult. Such fundamentally different gametes are produced through a fine-tuned balance between feminizing and masculinizing genes. For example, the switch to oogenesis requires repression of the fem-3 mRNA through the mog genes. Here we report on the cloning and characterization of the sex determination gene mog-2. MOG-2 is the worm homolog of spliceosomal protein U2A'. We found that MOG-2 is expressed in most nuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 63 publications
4
31
0
Order By: Relevance
“…We reasoned that if MOG proteins down-regulated fem-3 RNA, both proteins should not be found within the same germ cells. MOG proteins are present in the nuclei of many germ cells, including oocytes (Belfiore et al 2004;Kasturi et al 2010;Zanetti et al 2011). We show that FEM-3 labels the spermatogenic lineage.…”
Section: Fem-3 and Mog Expression Are Mutually Exclusivementioning
confidence: 73%
See 3 more Smart Citations
“…We reasoned that if MOG proteins down-regulated fem-3 RNA, both proteins should not be found within the same germ cells. MOG proteins are present in the nuclei of many germ cells, including oocytes (Belfiore et al 2004;Kasturi et al 2010;Zanetti et al 2011). We show that FEM-3 labels the spermatogenic lineage.…”
Section: Fem-3 and Mog Expression Are Mutually Exclusivementioning
confidence: 73%
“…Although several trans-acting repressors of fem-3 have been identified, the molecular mechanism of fem-3 repression remains speculative (Zhang et al 1997;Kimble 1999, 2000;Zanetti et al 2011). One study reported that in the absence of larp-1, fem-3(+) mRNA levels are increased (Zanin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As another example, the cell cycle regulators Cyclin E (CYE-1) and CDK2 (CDK-2) promote the proliferative fate (Fox et al, 2011; Jeong et al, 2011). A number of splicing factors have also been identified as being involved in regulating the proliferation vs. differentiation decision (Belfiore et al, 2004; Mantina et al, 2009; Kerins et al, 2010; Zanetti et al, 2011). Genetically, these splicing factors appear to function largely in the gld-1 pathway, functioning downstream of GLP-1/Notch signaling (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%